Analisis Problematika Standar Penilaian dalam Pendidikan Jasmani - Arisetya Purwadi, Dinda; Nanda Hanief, Yulingga; Erdilanita, Ulma (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Improving the quality of the assessment is needed because with an assessment process that meets the standards, student learning outcomes will be measured accurately. This article aims to analyze several studies on the problem of assessment standards in the physical education (PE) learning process so that knowing what factors have a relationship and influence on the occurrence of problems in physical education assessment standards and solutions that can be implemented in these problems. The method in this article is a literature review using flow chart PRISMA to identify articles through process filtering and data extraction. The results were obtained from 15 articles that meet the criteria, such as the subjects used are teachers and students in educational institutions and articles used in at least the last ten years. A total of 15 articles stated that the assessment process in physical education learning still needs a lot to meet the educational assessment standards. This is due to a lack of understanding of performance appraisal because teachers usually only see and use pre-existing assessments without evaluation and need to be adjusted to the character of student achievement and teachers' critical thinking without pedagogy.